Rethinking Language Use in Digital Africa : Technology and Communication in Sub-Saharan Africa - Leketi Makalela; Goodith White (Multilingual Matters, 2021)
This book challenges the view that digital communication in Africa is limited and relatively unsophisticated and questions the assumption that digital communication has a damaging effect on indigenous African languages. The book applies the principles of Digital African Multilingualism (DAM) in which there are no rigid boundaries between languages. The book charts a way forward for African languages where greater attention is paid to what speakers do with the languages rather than what the languages look like, and offers several models for language policy and planning based on horizontal and user-based multilingualism. The chapters demonstrate how digital communication is being used to form and sustain communication in many kinds of online groups, including for political activism and creating poetry, and offer a paradigm of language merging online that provides a practical blueprint for the decolonization of African languages through digital platforms. This book is open access under a CC BY NC ND licence.